Brodifacoum causes coagulopathy, hemorrhages, and mortality in rainbow trout (Oncorhynchus mykiss) at environmentally relevant hepatic residue concentrations - Hannah Schmieg; Hermann Ferling; Karina Annika Bucher; Stefanie Jacob; Julia Regnery; Hannah Schrader; Julia Schwaiger; Anton Friesen (Ecotoxicology and Environmental Safety)
Widely used second-generation anticoagulant rodenticides like brodifacoum are classified as persistent, bioaccumulative, and toxic. Widespread exposure of terrestrial and avian non-target species is well-known and recently hepatic anticoagulant rodenticide residues have been detected in wild fish. However, no sufficient data exist to interpret the effects of these findings on fish health. In order to assess the potential impact of rodenticide residues on fish, we exposed rainbow trout (Oncorhynchus mykiss) to brodifacoum-spiked feed. In a first experiment, individually kept trout (body weight ca. 200 g) were exposed to a single dose of brodifacoum and observed for 15 days. In a second experiment, fish (body weight ca. 330 g) were kept in groups and fed every 7 or 8 days with brodifacoum-spiked feed for up to 60 days. Sampling of trout every 15 days over the 60 days period allowed monitoring of brodifacoum concentrations in serum, liver, and muscle tissue, as well as occurring effects over the course of the experiment. In both experiments, brodifacoum doses of ≥ 75 µg/kg body weight caused prolonged or non-measurable blood coagulation times. Disturbed hemostasis led to hemorrhages and anemia with significantly decreased albumin levels. In the 60 days-experiment, brodifacoum doses ≥ 100 µg/kg body weight caused additionally discoloration, apathy, and anorexia, resulting in reduced weight gain, and ultimately mortality. The delay until the onset of overt symptoms (14–17 days) highlights the importance of test duration while investigating effects of anticoagulant rodenticides in fish. The lowest hepatic brodifacoum concentration associated with effects in trout was on average 122.6 ng/g liver wet weight, which is in the range of previously reported brodifacoum residues in wild fish. These findings illustrate the risks associated with the use of anticoagulant rodenticides for freshwater fish and reinforce the need to stipulate all available and appropriate risk mitigation measures to prevent emissions at source.